Republic of Poland : Arrangement Under the Flexible Credit Line; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director the Republic of Poland. (IMF Staff Country Reports; Country Report, 2010)
Poland's macroeconomic performance was strong in the decade leading up to the global crisis. Poland's commitments to the EU Stability and Growth Pact helped lower the fiscal deficit and limit government debt. Its strong financial supervisory framework helped foster a well-capitalized banking system. A successor Flexible Credit Line arrangement for Poland will play an important role in supporting the government's economic policy strategy. Although Poland's underlying fundamentals remain strong, there are risks to the near-term outlook, considering its large and open capital markets.